σI from Bacillus subtilis: Impact on Gene Expression and Characterization of σI-Dependent Transcription That Requires New Types of Promoters with Extended -35 and -10 Elements - Ramaniuk, Olga; Převorovský, Martin; Pospíšil, Jiří; Vítovská, Dragana; Kofroňová, Olga; Benada, Oldřich; Schwarz, Marek; Šanderová, Hana; Hnilicová, Jarmila; Krásný, Libor (Journal of bacteriology, 2018)
The σI sigma factor from Bacillus subtilis is a σ factor associated with RNA polymerase (RNAP) that was previously implicated in adaptation of the cell to elevated temperature. Here, we provide a comprehensive characterization of this transcriptional regulator. By transcriptome sequencing (RNA-seq) of wild-type (wt) and σI-null strains at 37°C and 52°C, we identified ∼130 genes affected by the absence of σI Further analysis revealed that the majority of these genes were affected indirectly by σI The σI regulon, i.e., the genes directly regulated by σI, consists of 16 genes, of which eight (the dhb and yku operons) are involved in iron metabolism. The involvement of σI in iron metabolism was confirmed phenotypically. Next, we set up an in vitro transcription system and defined and experimentally validated the promoter sequence logo that, in addition to -35 and -10 regions, also contains extended -35 and -10 motifs. Thus, σI-dependent promoters are relatively information rich in comparison with most other promoters. In summary, this study supplies information about the least-explored σ factor from the industrially important model organism B. subtilisIMPORTANCE In bacteria, σ factors are essential for transcription initiation. Knowledge about their regulons (i.e., genes transcribed from promoters dependent on these σ factors) is the key for understanding how bacteria cope with the changing environment and could be instrumental for biotechnologically motivated rewiring of gene expression. Here, we characterize the σI regulon from the industrially important model Gram-positive bacterium Bacillus subtilis We reveal that σI affects expression of ∼130 genes, of which 16 are directly regulated by σI, including genes encoding proteins involved in iron homeostasis. Detailed analysis of promoter elements then identifies unique sequences important for σI-dependent transcription. This study thus provides a comprehensive view on this underexplored component of the B. subtilis transcription machinery.
Keywords: Iron; bakteriální proteiny; Promoter Regions, Genetic; regulon; Operon; regulace genové exprese u bakterií; DNA-Directed RNA Polymerases; Transcription, Genetic; operon; Regulon; transkriptom; železo; promotorové oblasti (genetika); DNA řízené RNA-polymerasy; Bacillus subtilis; Bacterial Proteins; sigma faktor; Sigma Factor; Transcriptome; Gene Expression Regulation, Bacterial; genetická transkripce